2003
DOI: 10.1038/sj.bmt.1704075
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell transplantation for myelofibrosis: a report from two Canadian centers

Abstract: Summary:We describe the course of 25 patients with myelofibrosis (MF) due to agnogenic myeloid metaplasia (n ¼ 19) or essential thrombocytosis (n ¼ 6) who underwent allogeneic stem cell transplantation (SCT) at one of two Canadian centers. The median age at transplantation was 48.7 (IQR 45.9-50.4) years and transplantation was carried out at a median of 10.7 (IQR 5.67-26.5) months after diagnosis. Granulocyte engraftment (absolute neutrophil count 40.5 Â 10 9 /l) occurred at a median of 20 days after transplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 21 publications
4
60
2
Order By: Relevance
“…Several studies have been published [6][7][8][9][10][11][12][13][14][15][16]25 using either myeloablative or RIC regimens. The main finding is that a proportion of PMF can be controlled with an allogeneic transplant and long-term disease-free survival can be achieved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have been published [6][7][8][9][10][11][12][13][14][15][16]25 using either myeloablative or RIC regimens. The main finding is that a proportion of PMF can be controlled with an allogeneic transplant and long-term disease-free survival can be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16] Usually, PMF patients are referred for allogeneic HSCT when the Dupriez's risk score, 2 based on Hb and WBC count, is intermediate or high, whereas patients with a low-risk disease are usually monitored without treatment until progression. Other risk-assessment scores for transplant eligibility have been introduced.…”
Section: Introductionmentioning
confidence: 99%
“…Of the patients who failed primary engraftment one went on to have a second transplant from the same donor; two patients died from infection and one received donor lymphocyte infusion (DLI) and was alive 1 year after transplantation. The median times to neutrophil engraftment were 14 (9-25), 17 (9-25), and 13 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)) days for splenectomized patients and 20 (8-35), 19.5 (8-35), and 20 (14-35) days for those who had not had previous splenectomy in the total, MA and RIC groups, respectively. For the whole (P ¼ 0.008) and RIC (P ¼ 0.004) but not MA (P ¼ 0.333) groups previous splenectomy significantly reduced the time to engraftment in univariate analysis.…”
Section: Engraftmentmentioning
confidence: 99%
“…The use of conventional fully myeloablative (MA) conditioning regimens is associated with a high transplantation-related mortality (TRM) rate; [17][18][19][20][21] this is particularly seen in patients older than 45 years, 17 especially relevant given that PMF is most common in the middle-aged and elderly. Successful engraftment and disease remission have been shown using reduced-intensity conditioning (RIC) regimens in allogeneic SCT for PMF with apparently reduced TRM.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies using myeloablative regimens have shown that approximately 35-45% of patients achieve long-term cure from MF. [1][2][3] The curative potential of alloHCT is related to a combination of the reduction or eradication of the malignant clone by the conditioning regimen and a graft-versus-MF effect. A major barrier to alloHCT using conventional intensity conditioning (CIC) regimens is the high TRM observed in 30-45% of patients, which restricts the use of the procedure to a limited number of young and fit patients.…”
mentioning
confidence: 99%